ANALISIS KEUNGGULAN KOMPARATIF KAKAO DI PROVINSI SULAWESI BARAT - Samsuddin Samsuddin (Jurnal Agrotech, 2018)
Increased competitive advantage (competitiveness) of Indonesia cocoa becomes an important agenda in order face tight global competition. This research aimed (1) to determine the competitive advantage (Comparative Advantage) of cocoa commodities; (2) to investigate the competitive advantage of cocoa commodities (comparative advantage); (3. The research used a descriptivi-qualitative approach. The population included 5 regencies in West Sulawesi Province. The secondary data were obtained from the work force in the cocoa plantation in both West Sulawesi Province and lndonesia and from both the West Sulawesi Provincial Central Statistics Agency (BPS) and the National Central Statistics Agency. The analyses used were the Locational Qoutient (LQ) and SWOT analyses. The research results revealed that the cocoa commodities in West Sulawesi Province had a comparative advantage in the labor force in the cocoa plantation Sector. In general, since the last five years has the value of LQ> 1 or the average reaches 8.47. While the comparative advantage of the land area of cocoa based on a comparison with the Sulawesi area LQ value reached 2.99 in 2012. While the 2013-2014 experienced a drastic 0,95 and 0,89. That matter decline due to land conversion from cocoa to sawait.